Effect of Thallium(I) on Growth, Nutrient Absorption, Photosynthetic Pigments, and Antioxidant Response of Dittrichia Plants - Francisco Espinosa; Alfonso Ortega; Francisco L. Espinosa-Vellarino; Inmaculada Garrido (Antioxidants, 2023)
Dittrichia plants were exposed to thallium (Tl) stress (10, 50, and 100 µM) for 7 days. The Tl toxicity altered the absorption and accumulation of other nutrients. In both the roots and the leaves, there was a decline in K, Mg, and Fe content, but an increase in Ca, Mn, and Zn. Chlorophylls decreased, as did the photosynthetic efficiency, while carotenoids increased. Oxidative stress in the roots was reflected in increased lipid peroxidation. There was more production of superoxide (O2.−), hydrogen peroxide (H2O2), and nitric oxide (NO) in the roots than in the leaves, with increases in both organs in response to Tl toxicity, except for O2.− production in the roots, which fluctuated. There was increased hydrogen sulfide (H2S) production, especially in the leaves. Superoxide dismutase (SOD), ascorbate peroxidase (APX), dehydroascorbate reductase (DHAR), monodehydroascorbate reductase (MDHAR), and glutathione reductase (GR) showed increased activities, except for APX and MDHAR in the roots and GR in the leaves. The components of the ascorbate–glutathione cycle were affected. Thus, ascorbate (AsA) increased, while dehydroascorbate (DHA), reduced glutathione (GSH), and oxidized glutathione (GSSG) decreased, except for in the roots at 100 µM Tl, which showed increased GSH. These Tl toxicity-induced alterations modify the AsA/DHA and GSH/GSSG redox status. The NO and H2S interaction may act by activating the antioxidant system. The effects of Tl could be related to its strong affinity for binding with -SH groups, thus altering the functionality of proteins and the cellular redox state.